Orville Park, Park's Annotated Code of the State of Georgia 1914, Penal Code, Article 3, Carrying pistols without license, § 348(a)-(d) - (:unkn) unknown (General Publisher, 1910)
Prohibited the carry of any pistol or revolver without first obtaining a license from respective county in which the party resides. Subsections dictated how licenses were obtained and the cost of obtaining such licenses. Violators guilty of a misdemeanor.
--
Keywords: CARRY